2003
DOI: 10.1074/jbc.m309910200
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative Rab3D Mutants Reduce GTP-bound Endogenous Rab3D in Pancreatic Acini

Abstract: Immunocytochemical studies showed that while the wild-type Rab3D localized to zymogen granules, the two dominant negative mutants did not localize to granules and were primarily in the basolateral regions of the cell. The present study, therefore, evaluated the potential mechanisms by which the dominant negative mutants might act. An affinity precipitation assay based on the property of the Rab3 effector Rim1 to interact only with GTP-bound Rab3D was developed. 78.9 ؎ 4.5% of total endogenous Rab3D was found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 54 publications
2
53
0
Order By: Relevance
“…1). We also showed that VNUT co-localizes with Rab3D, which is a low-molecular weight GTP-binding protein that associates with secretory granules in exocrine glands, e.g., zymogen granules (ZGs) in pancreatic acini [9,21] (Fig. 1a, b).…”
Section: Vnut Expressionmentioning
confidence: 76%
See 1 more Smart Citation
“…1). We also showed that VNUT co-localizes with Rab3D, which is a low-molecular weight GTP-binding protein that associates with secretory granules in exocrine glands, e.g., zymogen granules (ZGs) in pancreatic acini [9,21] (Fig. 1a, b).…”
Section: Vnut Expressionmentioning
confidence: 76%
“…Rat acinar cell line AR42J (CRL-1492, ATCC, passages [15][16][17][18][19][20][21][22][23][24][25] was cultured in RPMI media supplemented with 10 % fetal bovine serum (FBS) and penicillin/streptomycin. Cells were cultured in humidified incubators at 37°C, with 5 % CO 2 in air.…”
Section: Cell Culture Of Ar42j Cellsmentioning
confidence: 99%
“…The precise function of rab3D in acinar secretion is still unclear although studies overexpressing active and dominant negative forms in pancreatic acini showed changes in exocytosis (Ohnishi et al, 1997;Chen et al, 2003). Surprisingly, recent generation of a rab3D knockout mouse resulted in no detectable phenotype in release kinetics in the exocrine pancreas or parotid gland (Riedel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise function of rab3D in acinar secretion is still in question, its association with mature SVs is decreased concomitant with apical exocytosis (Wang et al, 2003). Dominant negative forms of rab3D reduce amylase secretion in pancreatic acini (Chen et al, 2003), while overexpression of wild type rab3D can enhance pancreatic acinar exocytosis (Ohnishi et al, 1997), suggesting its direct participation in acinar exocytosis. Actin filaments in lacrimal acini can be detected in association with peripheral membranes, with considerable enrichment beneath the apical membrane due to actin concentration in the dense cortical apical actin array which includes microvilli (da Costa et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic secretory granules can be purified by Percoll gradient separation of a particulate fraction of pancreatic postnuclear supernantant (Chen et al, 2003). The dense white band of secretory granules was collected in fraction 3 of the Percoll gradient, and microscopic inspection of the Percoll gradient fractions confirmed that large vesicles around 1 m in diameter were enriched and abundant in this fraction ( Fig.…”
Section: Sdmg1 Is a Component Of Pancreatic Secretory Granulesmentioning
confidence: 93%